Hubungan Pengetahuan Ibu Tentang Retardasi Mental dengan Penerimaan Ibu yang Memiliki Anak Retardasi Mental Sedang di SDLB Negri Ciamis Tahun 2021 - Nadya Dewi; Daniel Akbar Wibowo (Universitas Galuh Ciamis, 2022)
Children are the most beautiful things given as a gift that must be cared for and cared. Mental retardation is a condition with less intelligence since the developmental period. Parents feel happy when given a perfect child but when given a less perfect child then the parents of both mothers will be disappointed not even able to accept the child. The purpose of the study was to find out the relationship between maternal knowledge and acceptance of mothers who have moderate mental retardation children. The research method used in this study was descriptive correlation, a sample used by 37 mothers who had moderate mental retardation children with total sampling techniques. The results found that most mothers had enough knowledge as much as 59.5% with a small percentage of positive acceptance rate of 27% and negative acceptance rate of almost half 32.4%, a small percentage of 18.9% have good knowledge with negative reception 5.4% and a small percentage have less knowledge and negative acceptance is 21.6%. So based on the results of statistical tests with a ƿ of 0.003 which means there is a relationship between maternal knowledge and acceptance of mothers who have moderate mental retardation children. Researchers suggest mothers are more active in their child's activities in order to create communicative relationships in order to help mothers accept the child's condition.